Informing climate mitigation policies - Malnar, Brina (Teorija in praksa, 2023)
The article presents a meta-analysis of academic articles using the European Social Survey Climate Change module. It summarises the key individual and country-level factors that shape climate beliefs, behaviours, and policy support, aiming to mitigate the problem of the fragmentation of findings when informing policymakers. The results, depicted in a heuristic model, underscore the significance of awareness, trust, and socio-political contexts, illustrating the intricate interplay of climate change beliefs, emotional engagement and policy preferences. By consolidating the scattered research through a meta-analytical approach, the study efficiently identifies key obstacles encountered by European decision-makers while implementing climate mitigation measures and policies.
Keywords: climate action; climate change; climate policy; ESS; Europena social survey; Evropska družboslovna raziskava; okoljske politike; okoljsko ravnanje; podnebne spremembe